The density of Braun’s Lipoprotein determines vesicle production in E. coli - Brian P. Weaver; Fengjie Zhao; Yuanli Gao; James Q. Boedicker; Christoph A. Haselwandter (PLoS ONE, 2025)
Production of extracellular vesicles by Gram-negative bacteria is known to be associated with blebbing of the outer membrane. Several proteins within Gram-negative bacteria crosslink the outer membrane to the cell wall, and thereby stabilize the cell envelope. Prior work in Escherichia coli demonstrated that crosslinking proteins reduce membrane blebbing and vesicle formation, and that deletion of crosslinking proteins, most notably Braun’s lipoprotein (Lpp), can increase vesicle production by about two orders of magnitude. To examine the quantitative relation between crosslinking proteins and bacterial vesicle formation, we develop here a simple physical model that predicts how vesicle production depends on the Lpp density. We test our model by measuring vesicle production in a strain of E. coli with tunable Lpp expression. Our experimental observations agree with our model predictions for most measured Lpp densities. For low Lpp densities, our experiments yield more pronounced vesicle production than predicted by our model, which can be explained if the mechanical properties of the cell envelope depend on the Lpp density. Our results shed light on basic principles and molecular mechanisms governing bacterial vesicle production.